Clear-cut free forestry among private forest owners in southern Sweden - Wemmer, Louice (2020)
Swedish forestry is dominated by the clear-cutting system. The use of alternative methods such as clear-cut free forestry is becoming of greater interest. The Swedish forest agency have a wish for a more varied forestry management and are currently working with programs to promote these kind of management methods. Although the interest is increasing there are so far few forest owners who manage their forest in this way, and the knowledge about their motivations and practice is scarce. To get a better understanding about these forest owners this study aims to answer the following questions; (I) What is clear-cut free forestry from the owners perception? (II) What motive explains private owners’ interest in clear-cut free forestry? (III) Information and advice – What is accessible and where, and how do the FOs’ perceive it? The study is based on qualitative interviews analyzed with thematic analysis. In total 9 private forest owners in the south of Sweden were interviewed. These forest owners were all managing or planning to manage all or parts of their forest clear-cut free. This study shows that there seems to be an inconsistency when it comes to the terminology describing the management method; many of the forest owners seem to not know exactly what terminology to use, or if everyone they talk to will understand what the terminology means. One of the main motives for using clear-cut free methods is tradition; the forest has been managed in this way for a long time. Other important factors are economy, recreation and avoiding clear-cuts. The challenges for these forest owners are mainly the skepticism they perceive when seeking counselling, and also the machine operators lack of knowledge and understanding. In order to continue increasing the interest and use of clear-cut free forestry this could be important focus areas.